MECHANISMS FOR INCREASING THE EFFICIENCY OF HUMAN CAPITAL IN THE LABOUR MARKET THROUGH THE USE OF ARTIFICIAL INTELLIGENCE (Журнал «Маркетинг», 2026)
This study examined the mechanisms through which artificial intelligence enhanced the efficiency of human capital in the labour market. Drawing on international reports, empirical research findings, and labour market statistics from Uzbekistan, the study evaluated the contribution of artificial intelligence to labour productivity, workforce reskilling, skills development, job matching, and labour market forecasting. The findings demonstrated that the effective application of artificial intelligence supported higher human capital efficiency, strengthened labour market competencies, and improved employment quality. The analysis also highlighted the importance of integrating AI-based approaches into workforce development and labour market institutions. The study provided practical implications for improving human capital policies and promoting sustainable labour market development.